'To donate or not to donate? that is the question!': an organ and body donation comic. (8th July 2020) - Irwin, Jessica; Roughley, Mark; Smith, Kathryn
Abstract: Conversations surrounding end of life and death can be difficult or taboo for some, meaning that matters of organ and body donation are not widely discussed. To Donate or Not to Donate? That is the Question! is a comic developed to raise awareness and challenge common misconceptions about donation by encouraging the publics to engage in informed discussions about the different options available. This case study proposes graphic medicine as an alternative method of presenting donation information to a public audience, and illustrates how the comic medium can communicate body donation information in an accessible and engaging way.